2012
DOI: 10.1038/ejhg.2012.278
|View full text |Cite
|
Sign up to set email alerts
|

Genomic correlates of variability in immune response to an oral cholera vaccine

Abstract: Cholera is endemic to many countries. Recent major outbreaks of cholera have prompted World Health Organization to recommend oral cholera vaccination as a public-health strategy. Variation in percentage of seroconversion upon cholera vaccination has been recorded across populations. Vaccine-induced responses are influenced by host genetic differences. We have investigated association between single-nucleotide polymorphic (SNP) loci in and around 296 immunologically relevant genes and total anti-lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…A single cell layer of the mucosal epithelium essentially regulates intestinal homeostasis [30]. This physical barrier is a prominent part of the innate immune system with damage-healing and infection-limiting properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single cell layer of the mucosal epithelium essentially regulates intestinal homeostasis [30]. This physical barrier is a prominent part of the innate immune system with damage-healing and infection-limiting properties.…”
Section: Discussionmentioning
confidence: 99%
“…0.05). We tested for existence of cryptic relatedness and population stratification using Eigenstrat [29]; no evidence was detected as all individuals formed a single cluster in the scatterplot of the first three principal components [30] ( figure 1). …”
Section: (B) Genomic Association Discovery and Validationmentioning
confidence: 99%
“…These genes with additional protein interactions are shown in this figure. Marco, TNFAIP3, and CXCL12are associated with the categories of epithelial barrier integrity, scavenger receptor family, intestinal homeostasis, and leukocyte attractant/recruitment [ 2 , 7 ]…”
Section: Figurementioning
confidence: 99%
“…Gene-environment interplay in immune phenotypes has been extensively studied using steady-state cellular immune profiles (13), functional immune responses (2,48), post-vaccination responses (9,10) and V,D and J usage biases in naïve and memory T and B cell compartments (11). Some of these studies have identified genomic correlates associated with specific steady-state immune phenotypes (2) and vaccine responses (12). However, there are conflicting findings regarding the relative importance of genetic versus environmental factors in regulation of immune phenotype (1,2,13,14), warranting further investigations at the population-level in humans and mechanistic studies in mice on regulation of individual immune phenotypes.…”
Section: Introductionmentioning
confidence: 99%